Preconditioning effects of photobiomodulation on repeated-sprint ability of professional basketball players - Giovanini, B.; Altimari, L. R.; de Paula Ramos, S.; Okazaki, V. H.; Okuno, N. M.; Junior, A. F. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to investigate the preconditioning effects of photobiomodulation on repeated-sprint ability of professional basketball players. Ten professional basketball players took part in this randomized, double-blind, placebo-controlled, crossover study. The subjects attended 2 repeated-sprint test sessions. In each session, the subjects performed a general warm-up, followed by a familiarization sprint. Afterward, the subjects received either the photobiomodulation (660 and 850 nm, 12 J/cm², 83.4 J per point, 10 points, light-emitting diode [LED] treatment) or placebo intervention and performed the repeated-sprint test. The repeated-sprint test consisted of ten 30-m sprints with 1 change of direction (15 + 15 m), interspersed by 30 seconds of passive recovery. Sprint times and heart rate responses were monitored during the test. To compare moments and conditions, linear mixed-effects models were applied with statistical significance set at p < 0.05, and Cohen's d was used as effect size (ES). The LED treatment could not improve total time (p = 0.662; ES = -0.06), best time (p = 0.869; ES = 0.02), fatigue index (p = 0.169; ES = 0.64), or sprint decrement (p = 0.124; ES = -0.75) when compared with the placebo condition. In addition, mean heart rate (p = 0.687; ES = 0.07) and maximal heart rate (p = 0.837; ES = -0.03) were similar between conditions. We concluded that the LED condition could not improve the repeated-sprint ability of professional basketball players.